LAMARAN (KHITHBAH) DALAM PERNIKAHAN PERSPEKTIF PENDIDIKAN ISLAM - Mawardi Mawardi; Shokhibul Mighfar; Rahwan Rahwan (Fakultas Syariah dan Ekonomi Islam, Universitas Ibrahimy, 2022)
The values of Islamic education are the development of the human mind and the arrangement of behavior and emotions based on Islamic teachings. Thus, Islamic education's values will provide humans with happiness, welfare and human safety both in this world and in the afterlife. According to the Islam viewpoint, everyone must prepare themselves as well as possible to build a relationship based on love and noble values. Physical, mental, and economic preparedness is required; in this situation, in terms of the educational features inherent in Islamic teachings, the objective is to build a secure, pleasant, and tranquil home environment.